Color Tuning Using Scanning Optical Tweezers - Benjun Yao; Shun Yuan; Guowei Yang; Hongxiang Lei (Advanced Photonics Research, 2023)
Color tuning plays an increasingly vital role in daily life, including painting, printing, decoration, and animation display. Among many nonemissive color tuning technologies with low‐cost and low‐energy consumption, direct color mixing is simpler without fine and complex display structural designs or specific synthetic materials. Nevertheless, it yet faces an enormous challenge in precise color tuning due to high requirement for integrating dyes in a designable way. Herein, a scanning optical tweezers‐based color mixing method is proposed for precise color tuning. Water/oil‐soluble dye microdroplets with different sizes and colors can be stably captured and then rapidly fused by setting and exerting different trajectories of optical traps under optical tweezers. Thus, the color hue, saturation, and value of the mixed microdroplet can be accurately tuned. Besides, this is further applied to the optical assembly of colorful patterns in a programmable manner. The proposed method is more effective in harvesting pure color and high color quality without introducing exogenous materials contaminating the sample during the manipulation process, which is believed to have potential applications in liquid animation, human–robot interactive painting, and color sensing.